Associação entre polimorfismos em genes envolvidos no metabolismo do folato e risco materno para a síndrome de Down - Mendes, Cristiani Cortez (2011)
Down syndrome is the most common genetic disorder and, in about 90% of the cases, is characterized by free trisomy of chromosome 21, caused by the failures of chromosomal segregation during maternal meiosis. Studies suggested that the occurrence of DS independent of maternal age is associated with DNA hypomethylation due to impairments in folate metabolism, and genetics polymorphisms involved in this metabolic pathway have been appointed as maternal risk factors for DS. Addition to the genetic polymorphisms, micronutrients deficiencies, as folate and B12 vitamin, can change the products of the folate pathway and result in DNA hypomethylation, genomic instability and reduced DNA repair capacity. Objectives: We evaluated the influence of the 19-base pairs (bp) deletion polymorphism of Dihydrofolate reductase (DHFR) gene, DNA methyltransferase 3B (DNMT3B) -149C→T and -283T→C on the maternal risk for DS and investigated the association between these polymorphism and variations in the concentrations of serum folate and plasma homocysteine (Hcy) and methylmalonic acid (MMA). Methods: 105 mothers of DS individuals with free trisomy 21 and 185 mothers of individuals without the syndrome were studied. Molecular analysis of the DHFR polymorphism was performed by the Polymerase Chain Reaction (PCR) by difference in the size of fragments and DNMT3B -149C→T and -283T→C were analyzed by real-time PCR. Folate was quantified by chemiluminescence and Hcy and MMA by liquid chromatography-tandem mass spectrometry. Results: The analysis of DHFR polymorphism showed no difference between the groups in relation to allele and genotype frequencies (P = 0.44; P = 0.69, respectively). In relation to gentoype, folate, Hcy and MMA concentrations did not differ between the groups (P > 0.05). The DNMT3B -149TT/-283TC combined genotypes were associated with increased maternal risk for DS (OR = 4.61, CI 95% = 1.35 15.79; P = 0.02) and higher folate concentration was observed in mothers with DNMT3B -149CT/-283CC genotypes compared to other combined genotypes (P = 0.03). Conclusions: The 19-bp deletion polymorphism of DHFR gene is not a maternal risk factor for DS and is not related to variations in the concentrations of serum folate and plasma Hcy and MMA. On the other hand, the DNMT3B polymorphisms increase the maternal risk for DS and modulate the folate concentration in studied population.